Die Fachgruppe „Musikethnologie und vergleichende Musikwissenschaft“ in der Gesellschaft für Musikforschung: Stationen – Positionen – Perspektiven - Fuhr, Michael; Gruber, Cornelia (Die Musikforschung, 2023)
This article gives a brief insight into the work of the study group “Ethnomusicology and Comparative Musicology” of the “Gesellschaft für Musikforschung” (GfM). It spotlights central issues, historical moments and developments in the past, and more recent activities of the study group. The first part roughly outlines cornerstones from its founding stages in the post-WWII years, when traditional views of “Völkerkunde” prevailed, to the paradigm shifts of the 1980s and 1990s, as comparative musicology gradually shifted towards ethnomusicological approaches grounded in cultural and social anthropology. The second part highlights the study group’s self-reflexive perspective and its recent engagement with topics such as diversity, anti-racism, and (post-)coloniality in the academic field. Drawing on issues discussed in the context of the “crisis of ethnographic representation,” recent debates and activities in the group are driven by ethical and political discussions regarding the power imbalances that shape ethnomusicological methodologies, practices and discourses within and beyond academia, and are thus closely tied to larger questions of social justice, equity, and inclusion.